PERSPECTIVE OF STUDENT INTEREST TOWARDS ONLINE CREDIT SERVICES - Ely Suhayati; Cun Figitria Panca Rhema (Accounting Department, Politeknik Negeri Bandung, 2024)
This research aims to determine the Interest of Students, Interest Rates, and Online Credit Decision both partially and simultaneously on the Usage of Online Credit Services. The research method used is descriptive and verificative with a quantitative approach. The data used are primary data, including the distribution of questionnaires and responses from the respondents under study. The sampling technique used is purposive sampling. Based on the criteria available, 100 student respondents from the management program at Unikom were obtained as research samples. The analysis design used is path analysis, correlation coefficient analysis, and determination coefficient analysis, while hypothesis testing uses t-tests and Ftests. The research results indicate that, partially, Student Interest has a significant positive effect on the Usage of Online Credit Services. Interest Rates have a significant positive effect on the Usage of Online Credit Services. Credit Decision has a significant negative effect on the Usage of Online Credit Services. The F-test results show a significant positive influence on Student Interest, Interest Rates, and Online Credit Decision, both partially and simultaneously, on the Usage of Online Credit Services